Electrospun Biopolyesters: Hydrophobic Scaffolds with Favorable Biological Response - Pedram Azari; Samira Hosseini; Belinda Pinguan Murphy; Sergio O. Martinez-Chapa (Journal of Public Health International, 2018)
This article reviews electrospun biopolyester scaffolds, focusing on surface hydrophobicity, cell response, and applications in tissue engineering.
Keywords: electrospun biopolyester scaffolds